On the S-Invariance Property for S-Flows - Amin Saif; Adem Kılıçman (Abstract and Applied Analysis)
We define an equivalence relation on a topological space which is acted by topological monoid S as a transformation semigroup. Then, we give some results about the S-invariant classes for this relation. We also provide a condition for the existence of relative S-invariant classes.